L’archeologia preventiva come ambito professionale - Cristina Anghinetti (GEOmedia)
Preventive archaeology has increased the number of work possibilities in design and execution. The archaeologist must acquire a new professional mentality, open to dialogue with other professional figures. This theme includes collaboration on interventions in OG2 and participation in the construction of spatial planning tools. The open professional horizon projects the archaeologist into the world of actual design, putting him in a position to provide proposals, solutions and produce work that can be understood by other designers and those who will have to carry out the work.